2007
DOI: 10.5194/hess-11-1785-2007
|View full text |Cite
|
Sign up to set email alerts
|

GIBSI: an integrated modelling system for watershed management – sample applications and current developments

Abstract: Abstract. Hydrological and pollutant fate models have long been developed for research purposes. Today, they find an application in integrated watershed management, as decision support systems (DSS). GIBSI is such a DSS designed to assist stakeholders in watershed management. It includes a watershed database coupled to a GIS and accessible through a user-friendly interface, as well as modelling tools that simulate, on a daily time step, hydrological processes such as evapotranspiration, runoff, soil erosion, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 23 publications
(25 reference statements)
0
19
0
1
Order By: Relevance
“…Since 1998, several applied studies have been conducted. Numerous upgrades to this integrated modeling system have been added since inception [17].…”
Section: Gibsi Softwarementioning
confidence: 99%
“…Since 1998, several applied studies have been conducted. Numerous upgrades to this integrated modeling system have been added since inception [17].…”
Section: Gibsi Softwarementioning
confidence: 99%
“…The conceptual parameters such as CN 2 in the SCS curve method are defined as the conceptualization of a non-quantifiable process, and determined by the process of model calibration. Conversely, physical parameters can be measured or estimated based on watershed characteristics when intensive data collection is possible (Vertessy et al, 1993;Nandakumar and Mein, 1997). Because of the unknown spatial heterogeneity of a studied area and the expensive experiments which may be involved, the physical parameters are usually determined by calibrating the model against the measured data (Raat et al, 2004).…”
Section: Z Y Shen Et Al: a Case Study Of Swat Model Applied To Thrmentioning
confidence: 99%
“…It has been shown that parameter uncertainty is inevitable in hydrological modeling and a corresponding assessment should be conducted before model prediction in the decision making process. Studies of parameter uncertainty have been conducted in the area of integrated watershed management (Zacharias et al, 2005), peak flow forecasting (Jorgeson and Julien, 2005), soil loss prediction (Cochrane and Flanagan, 2005), nutrient flux analysis (Murdoch et al, 2005;Miller et al, 2006), assessment of the effect of land use change (Eckhardt et al, 2003;Shen et al, 2010;Xu et al, 2011) and climate change impact assessment (Kingston and Taylor, 2010), among many others. Nevertheless, parameter identification is a complex, non-linear problem and numerous possible solutions might be obtained by optimization algorithms (Nandakumar and Mein, 1997).…”
Section: Z Y Shen Et Al: a Case Study Of Swat Model Applied To Thrmentioning
confidence: 99%
See 2 more Smart Citations